Diagnosing cerebral palsy in full‐term infants. (7th October 2018) - Morgan, Catherine; Fahey, Michael; Roy, Bithi; Novak, Iona
Abstract: More than 50% of infants with cerebral palsy (CP) are born at or near term, with the vast majority having pre‐ or perinatally acquired CP. While some have a clinical history predictive of CP, such as neonatal encephalopathy or neonatal stroke, others have no readily identifiable risk factors. Paediatricians are often required to discriminate generalised motor delay from a variety of other diagnoses, including CP. This paper outlines known causal pathways to CP in term‐born infants with a focus on differential diagnosis. Early and accurate diagnosis is important as it allows prompt access to early intervention during the critical periods of brain development. A combination of clinical history taking, standard clinical examination, neuroimaging and genetic testing should be started at the time of referral. Attention to the investigation of common comorbidities of CP, including feeding and sleep difficulties, and referral to early intervention are recommended.